ACTION GAMES ARE A FACTOR THAT INCREASES THE PHYSICAL FITNESS AND HEALTH OF GIRLS - Khamroqulov Rasuljon; Rakhmatova Mukhtasarkhon (Journals Park Publishing, 2022)
This article talks about the fact that action games are one of the important factors that increase the physical fitness and health of girls.
Keywords: tradition, cooking, example, upbringing, sewing